PENGGUNAAN MEDIA SOSIAL PADA MAHASISWA UNIVERSITAS KRISTEN PETRA SURABAYA - Monica, Vita; Rosari, Regina Bella (Institute of Research and Community Outreach - Petra Christian University, 2019)
In the midst of the times and technological growth, the function of mass media began to be carried out by social media. This is influenced by the rapid development of various types of social media and its features. Most social media users are millennials. One of the millennial generation members and active users of social media are students, including Petra Christian University students. This study is using survey method, aims to determine using of Facebook, Twitter, Instagram, YouTube, and LinkedIn by 225 Petra Christian University students. From this study is known, the majority of students use Instagram. They used Instagram to get information, find entertainment, add networking, and increase knowledge